LIMITATION OF THE AUTHORITY OF THE DISTRICT OR CITY LAND OFFICE IN THE ISSUANCE OF BUILDING USE RIGHTS CERTIFICATES (HGB) - Rr. Dini Indriyanti; Sunardi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The issuance of Building Use Rights Certificates (HGB) by Regency/Municipal Land Offices is part of the public service function aimed at providing legal certainty over land utilization. However, in practice, the authority of regional Land Offices has been subject to certain limitations, particularly regarding land with specific criteria that must be processed at the Regional Office or the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN). This situation potentially leads to service delays, legal uncertainty, and administrative burdens for both the public and business actors. Based on these issues, this research formulates two main problems: (1) how the restriction of authority affects the quality of land services and legal certainty; and (2) what legal consequences arise from the limitation of authority of Regency/Municipal Land Offices in the process of issuing HGB certificates. This study employs a normative juridical method with statutory and conceptual approaches. Primary legal materials consist of land regulations and related legal documents, complemented by secondary legal materials such as literature and scholarly journals. The analytical techniques used are legal interpretation and legal construction to assess the consistency between normative provisions and service implementation. The results indicate that the limitation of authority is based on the principles of administrative prudence and vertical supervision to prevent abuse of power. However, its implementation creates obstacles in public service delivery through longer bureaucratic procedures, thereby reducing the effectiveness of land services and generating potential legal uncertainty. Therefore, a clearer coordination mechanism, standardized procedures, and enhanced transparency are needed so that the restriction of authority maintains legality without hindering public service and legal certainty.